If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2v + 29 = 9(v + 9) Reorder the terms: 29 + 2v = 9(v + 9) Reorder the terms: 29 + 2v = 9(9 + v) 29 + 2v = (9 * 9 + v * 9) 29 + 2v = (81 + 9v) Solving 29 + 2v = 81 + 9v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-9v' to each side of the equation. 29 + 2v + -9v = 81 + 9v + -9v Combine like terms: 2v + -9v = -7v 29 + -7v = 81 + 9v + -9v Combine like terms: 9v + -9v = 0 29 + -7v = 81 + 0 29 + -7v = 81 Add '-29' to each side of the equation. 29 + -29 + -7v = 81 + -29 Combine like terms: 29 + -29 = 0 0 + -7v = 81 + -29 -7v = 81 + -29 Combine like terms: 81 + -29 = 52 -7v = 52 Divide each side by '-7'. v = -7.428571429 Simplifying v = -7.428571429
| x^2-25x+150= | | 6x+0.3= | | 3x-2.5+4=4.5+x | | -42=-7 | | 118x=1/3 | | 46+7.3g=46.0365 | | 5(4x-7)=-21(5-x) | | 1/3x=118 | | (8h-1)-(h+3)h=-3 | | y=(2x-1)/(4) | | 5/6(6t-6)-3 | | 2(96+l)+2(60+w)= | | -7u+5(u-2)=-14 | | 118x=2/3 | | 3b+14=11 | | pq=y | | 6x+8x-5=23 | | Lnx-7=-3.2 | | 2x+36y=-1 | | 1=2n-n | | 12x+1=3(4x+1) | | 6(d+9)=90 | | y=2x-1/4 | | k/3-3=4 | | Q/4-1=5 | | 2x-4+0.2+0.3=7 | | X+6.2=9.1 | | 11f-(-2f+2)f=.5 | | X^2-2x+x-2=54 | | 1/2y=x=6 | | 9(c-88)=63 | | 4log(3x)=15 |